THE ROLE OF RETURN ON ASSETS AND DEBT TO EQUITY RATIOS AS A BASIS FOR DETERMINING STOCK RETURNS - Albart, Nicko; purnomo, hadi (Universitas Dharma Wacana, 2023)
Financial ratios are relative and can provide a more in-depth view of the financial condition of a business entity. The study examines the effect of Return on assets (ROA) and Debt to Equity Ratio (DER) on Stock Returns in Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange. The population in this study were food and beverage sub-sector manufacturing companies listed on the IDX during the 2018-2022 period. Sampling was done by purposive sampling method with a sample of 11 companies. The type of data used is secondary data obtained from company financial reports and annual reports, which can be accessed through the official website of the Indonesia Stock Exchange (www.idx.co.id) or the official website of the company. The data analysis technique used is multiple linear regression. The results show that ROA has an effect on stock returns with coefficient of 0,64, meaning that if ROA increases by 1%, it will increase stock returns by 0.64%. Furthermore, DER has an affect on stock returns with coefficient of -0.057, meaning that if DER increases by 1%, it will decrease stock returns by 0.057% in Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange.